Hybrid seed production of bitter gourd is a remunerative venture - Jat, G S; Tomar, B S; Muthukumar, P; Kumar, Mukul; Singh, Balraj (Indian Horticulture, 2019)
Under open field condition, the seed yield and seed quality of bitter gourd is drastically reduced due to biotic stresses including, incidence of viral diseases (bitter gourd mosaic virus) and fruit fly attack in kharif season and abiotic stresses including changing environmental conditions like early onset of high temperature, unseasonal rains during summer season which restricts hybrid seed production of bitter gourd under north Indian conditions. The plant growth and reproductive characters like female flower production, fruit set and fruit developments are greatly affected by these factors resulting in low seed yield and quality. Thus, making hybrid seed production economically viable under north Indian condition is a challenging task. The seed crop grown under insect proof net house overcomes the threat of insect vectors, viral diseases and unfavourable climatic conditions, therefore, helps in attaining the better seed yield and quality.